Enucleation versus hepatectomy for hepatic hemangiomas: A meta-analysis - Jiang, Bin; Shen, Zheng-Chao; Fang, Xiao-San; Wang, Xiao-Ming (Frontiers in Surgery, 2022)
Objective To compare the safety and efficacy of enucleation and hepatectomy for the treatment of hepatic hemangioma (HH). Methods A systematic literature search was conducted to identify studies evaluating enucleation versus hepatectomy for HH starting from the time of database creation to February 2022. Extraction of the data used in this study was done from the literature. The differences between the two surgical approaches were evaluated by comparing and analyzing the relevant data by means of meta-analysis. Results A total of 1,384 patients (726 underwent enucleation, and 658 with hepatectomy) were included in our meta-analysis from 12 studies. Enucleations were associated with favorable outcomes in terms of operation time [mean difference (MD): −39.76, 95% confidence interval (CI): −46.23, −33.30], blood loss (MD: −300.42, 95% CI: −385.64, −215.19), length of hospital stay (MD: −2.33, 95% CI: −3.22, −1.44), and postoperative complications (OR: 0.57, 95% CI: 0.44–0.74). There were no differences between the groups in terms of patients needing transfusion (OR: 0.85, 95% CI: 0.50, 1.42), inflow occlusion time (MD: 1.72, 95% CI: −0.27, 3.71), and 30-day postoperative mortality (OR: 0.23, 95% CI: 0.02–2.17). Conclusion Compared with hepatectomy, enucleation is found to be effective at reducing postoperative complications, blood loss, and operation time and shortening the length of hospital stay. Enucleation is similar to hepatectomy in terms of inflow occlusion time, 30-day postoperative mortality, and patients needing transfusing to hepatectomy.